1992
DOI: 10.1002/hep.1840150617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simvastatin, Ursodeoxycholic Acid and Simvastatin Plus Ursodeoxycholic Acid on Biliary Lipid Secretion and Cholic Acid Kinetics in Nonfamilial Hypercholesterolemia

Abstract: It has been recently shown that the newest hypocholesterolemic agent, simvastatin, lowers the biliary cholesterol saturation index and that its association with ursodeoxycholic acid renders it more effective. To determine the mechanism by which simvastatin decreases the biliary cholesterol saturation index, we evaluated hepatic secretion rates of cholesterol, bile acids and phospholipids, and cholic acid pool size, turnover and synthesis in eight hyperlipidemic patients (five women and three men, age range = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 44 publications
3
34
1
Order By: Relevance
“…Patients volunteered for the lithogenicity of bile. [4][5][6][7] It has been suggested that the reduc-study, which had been approved by the ethics committee of our hospition of biliary cholesterol secretion is caused by increased tal. conversion of cholesterol to bile acids 8 and malabsorption of Lipid Analysis.…”
Section: Methylase Steps Resulting In Decreased Biliary Secretionmentioning
confidence: 99%
“…Patients volunteered for the lithogenicity of bile. [4][5][6][7] It has been suggested that the reduc-study, which had been approved by the ethics committee of our hospition of biliary cholesterol secretion is caused by increased tal. conversion of cholesterol to bile acids 8 and malabsorption of Lipid Analysis.…”
Section: Methylase Steps Resulting In Decreased Biliary Secretionmentioning
confidence: 99%
“…UDCA, as an endogenous tertiary bile acid in man, has several biologic effects, such as inhibition of cholesterol absorption in the intestine [36] and inhibition of bile secretion [37] , stabilization of cell membrane [38] and modulation of immunologic reactions [39] . Recent reports suggested that the novel bile acid derivatives induce apoptosis via a p53-independent pathway in human breast carcinoma cells [8] .…”
Section: Discussionmentioning
confidence: 99%
“…It also reduces the cholesterol content of bile relative to bile acid and lecithin, a change that might theoretically be conducive to prevention or dissolution of cholesterol gallstones (2,3). Two related drugs, simvastatin and pravastatin, appear to have similar effects (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%